Pengelolaan Tanah Adat Gampong Menurut Hukum Adat Di Kecamatan Manggeng Kabupaten Aceh Barat Daya - Nora Azura; Dara Quthni Effida (Prodi Ilmu Hukum, Universitas Teuku Umar, 2023)
Southwest Aceh is one of the districts that has customary land, the result of community consultations regarding the management of customary land, the community is able to manage with a maximum land limit of 1 hectare per person on condition that it cannot be traded. This study aims to determine and explain the management of village customary land according to customary law and the existence of village customary land ownership rights according to customary law in Manggeng District, Southwest Aceh Regency. The method in this research is juridical empirical. The results showed that the Management of Gampong Customary Land According to Customary Law in Manggeng District, Aceh Barat Daya Regency was carried out in a structured and open manner where customary ownership rights were joint property rights based on village law and authority where the land was managed by the village government. Deliberations on customary law in the gampong can be carried out with several provisions including: 1) The community manages the customary land of the gampong in turns. 2) Each community can manage for 1 year or 2 harvests. 30 The results of the management are divided into 2 (two) where 50% is for the manager and 50% for the village treasury. 3) If the provisions are violated, then the sanctions will not be justified again. The existence of Hak Milik on Customary Land according to customary law has existed, grown and developed along with the development of the area itself. Customary property rights are applied from generation to generation in the life of legal alliances that are spread throughout the territory in Indonesia. Customary property rights have received constitutional recognition along with the recognition of customary law and indigenous peoples.